Case Report: Long-term observations from the tacrolimus weaning randomized clinical trial depicts the challenging aspects for determination of low-immunological risk patients - Masset, Christophe; Dantal, Jacques; Soulillou, Jean-Paul; Walencik, Alexandre; Delbos, Florent; Brouard, Sophie; Giral, Magali; , the Nantes DIVAT Consortium; Blancho, Gilles; Branchereau, Julien; Cantarovich, Diego; Cesbron, Anne; et al. (Frontiers in Immunology, 2022)
Whilst calcineurin inhibitors (CNI) are the cornerstone of immunosuppressive maintenance therapy in kidney transplantation, several studies have investigated the safety of CNI withdrawal in order to avoid their numerous side effects. In this context, we performed several years ago a clinical randomized trial evaluating CNI weaning in stable kidney transplant recipients without anti-HLA immunization. The trial was interrupted prematurely due to a high number of de novo DSA (dnDSA) and biopsy proven acute rejection (BPAR) in patients who underwent tacrolimus weaning, resulting in treatment for rejection and resumption of tacrolimus. We report here the long-term outcomes of patients included in this clinical trial. Ten years after randomization, all patients are alive with a functional allograft. They all receive tacrolimus therapy except one with recurrent cutaneous neoplasia issues. Long-term eGFR was comparable between patients of the two randomized groups (46.4 ml/min vs 42.8 ml/min). All dnDSA that occurred during the study period became non-detectable and all rejections episodes were reversed. The retrospective assessment of HLA DQ single molecule epitope mismatching determined that a majority of patients who developed dnDSA after tacrolimus withdrawal would have been considered at high immunological risk. Minimization of immunosuppression remains a challenging objective, mainly because of the issues to properly select very low immunological risk patients. Valuable improvements have been made the last decade regarding evaluation of the allograft rejection notably through the determination of numerous at-risk biomarkers. However, even if the impact of such tools still need to be clarify in clinical routine, they may permit an improvement in patients’ selection for immunosuppression minimization without increasing the risk of allograft rejection.